FINANCIAL AND ECONOMIC SECURITY OF HIGHER EDUCATION INSTITUTIONS IN THE MECHANISM OF SOCIAL POLICY IMPLEMENTATION - NYZHNYK, VIKTOR; NYZHNYK, IRYNA; LYSAK, VIKTOR (Herald of Khmelnytskyi National University. Economic sciences, 2021)
Educational policy as a component of social is considered in the context of the state and its institutions, local governments, legislation, financial and organizational support for the functioning and development of the education sector. High levels of education and science can create certain conditions for solving many social problems. Funding for education is seen as a payment for the positive externalities that benefit society as a whole. Investing in education saves some money in the development and maintenance of other areas of the national economy. Therefore, improving the financial and economic security of higher education institutions is an urgent issue of state social policy. All other spheres of social infrastructure of the national economy will develop to the same extent as the financial and economic activity of the higher education institution will be secured.The article considers the experience of higher education institutions in the direction of forming the structure of financial and economic security. The authors analyzed the components that are part of the financial and economic security of the institution of higher education and the elements that include each of the components. The article considers the features of each component in the structure of financial and economic security of higher education institutions. Given the current threats to the financial and economic security of the institution of higher education, the authors propose the main directions of its increase.In the article the authors to the main components of financial and economic security of higher education include the following components: financial and investment, educational and methodological, intellectual and personnel, material and technical, regulatory, energy, information and communication, technical and technological, security and socio-cultural. The authors outline that the definition of a specific list of components of financial and economic security of a particular higher education institution should be based on the principles of including the most important indicators that characterize the overall level of financial and economic security and reflect the real state of the institution and their calculation using reporting and public data.
Keywords: financial and economic security; components of financial and economic security; management of a higher education institution; mechanisms for implementing social policy